The Development of Health Education Learning Material Accordingly to Curriculum 2013 of Junior/Islamic Junior High School of Bergas District in Semarang Regency (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The purposes of the research are to create learning material product of health education in the level of junior/Islamic junior high school based on Curriculum 2013 and to analyze the effectiveness of the learning material development of health education toward the students and the teachers in the level of junior/Islamic junior high school. It is a Research & Development to create a product and to test the effectiveness of the product. The finding of the research is the product development of health education learning material for VII, VIII, and IX grades accordingly to Curriculum 2013 of Junior High Schools in Bergas district. The results of expert evaluation of the data analysis are: (1) the expert score of health education was 81.81%, (2) the expert score of physical education was 79.54%, (3) the expert score of media and language was 88.63%. The data analysis and evaluation of physical-health and sports teacher in Bergas district gained percentage 77.84%. The small test in Islamic Junior High School Al Uswah, Bergas gained percentage 82.91%, and the result of larger scale test in Public Senior High School Bergas gained percentage 86.35%. The conclusion is health education learning material product development for VII, VII, and IX grades were effective to be applied to the students of Junior/Islamic Junior High School in Bergas district.